Influence of aluminum nanoparticles and binders on the laser initiation of cyclotrimethylenetrinitramine. (December 2019) - Ji, Xiangbo; Tang, Duo; Li, Yong; Xing, Zongren; Wang, Yao; Wang, Liang; Gao, Yuan; Qin, Wenzhi
Highlights: The addition of Al nanoparticles can significantly improve the light absorption. The laser initiation energy of RDX can be reduced to 1.5 J/cm 2 with 2.0% Al nanoparticles. PVA, PVB, and F2314 were added into RDX as binders to prepare the RDX-based composite explosives. The binders hindered the heat transmission from aluminum nanoparticles to RDX explosive. Abstract: Aluminum nanoparticles were added into cyclotrimethylenetrinitramine (RDX) to enhance the laser absorption and lower the initiation energy of pulse laser. Polyvinyl acetate (PVA), polyvinyl butyral (PVB), and fluororubber (F2314) were added into RDX as binders to prepare the RDX-based composite explosives with desirable mechanical behavior. The influence of aluminum nanoparticles and binders on the light absorption, thermal behavior, laser initiation energy and the electron temperature in aluminum plasma were investigated using reflectance spectroscopy, differential scanning calorimetry, laser initiation and laser-induced breakdown spectroscopy. Results showed that the addition of aluminum nanoparticles could prominently lower the laser initiation energy of the RDX-based explosives. The RDX doped with 2.0% aluminum nanoparticles could be reliably initiated with 1.5 J/cm 2 laser energy (1064 nm, 8 ns). The laser initiation energy increased to 1.7, 2.4 and 2.9 J/cm 2 with the additions of 0.5%, 1.0% and 2.0% F2314 binders, respectively. When the addition of PVA and PVB increased to 2.0%, the RDX-based explosives couldn't be initiated by pulse laser. When the pulse laser radiated on the surface of the RDX-based composite explosives, the aluminum nanoparticles absorbed the laser energy and were heated to high temperature to initiate the explosives. The addition of binders can provide desirable mechanical behavior, but the laser initiation energy increased because the heat transmission from aluminum nanoparticles to RDX was hindered.